Prevalence of Cyberbullying in the New Normal of Learning: Implications to Higher Education Institutions - Asio, John Mark R.; Dojello, Sherly DR.; Etrata-Filio, Rosalyn; Santos, Jackie Lyn M.; Capiral, Christine Ivy S.; Monzales, Rosalie P.; Patiam, Aljay Marc C.; Elpedes, Jefferson; Ambrosio, Aura Julia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
In the advent of the “new normal” during the pandemic era, strategies to teach and learn switched to online. Students’ behavior and attitude also shifted from face-to-face to online. This study aims to assess the students' profiles and the prevalence of cyberbullying in the higher education institutions in Central Luzon, Philippines. The study used a descriptive-correlational technique with the help of an online survey to gather data. Using a convenience sampling technique, 300 higher education students participated in the online survey during the first semester of 2021–2022. In order to attain the objective of the study, the investigators used a standardized instrument. With the help of SPSS 23, the data analyst analyzed the gathered data using the following statistical tools: frequency, weighted mean, and non-parametrical tests like Kruskal-Wallis, Mann-Whitney U, and Spearman rho. The investigator found that the student-respondents were "never" cyberbullying victims or offenders. Furthermore, statistical inferences showed a variation for cyberbullying offenders as to age and sponsorship/scholarship and a weak indirect relationship between cyberbullying offenders and sponsorship/scholarship characteristics of the students. The investigators recommended pertinent implications for the new normal of learning among students and the institution from the study results.